Spine Expert Panel Review for Medical Decision Making: Laminectomy/Fusion Versus Laminectomy Alone. (16th November 2020) - Ghogawala, Zoher; Dunbar, Melissa; Kanter, Adam S; Albert, Todd; Bisson, Erica F; Wang, Marjorie C; Resnick, Daniel K; Mummaneni, Praveen V; Glassman, Steven D; Polly, David W; Bydon, Mohamad; Fehlings, Michael G; et al.
Abstract: INTRODUCTION: Recent published RCTs have created uncertainty around the appropriate utilization of lumbar fusion when performing a laminectomy for symptomatic lumbar degenerative spondylolisthesis. SLIP II is an RCT that aims to determine if spinal expert review might help to optimze patient experience and outcome when contemplating surgery for spondylolithesis. METHODS: We performed a multi-center prospective RCT at 15 sites. Patients (ages 18–85) with symptomatic lumbar stenosis with degenerative spondylolithesis were enrolled from 2017–2018. An interim analysis was planned when 100 patients had reached 6 month follow-up. Patients were randomized to either receive an expert spinal panel review of their case or not. Spinal expert review consisted of 10–15 surgeons' review of patient images and history regarding appropriateness of fusion that was shared with both treating surgeon and patient. Outcome assessments (EQ-5D and ODI) were assessed pre-operatively, 3 months, and at 6 months. NASS patient satisfaction was also assessed after surgery. RESULTS: Thirteen sites randomized 100 patients - 64 (review) and 36 (no review). Mean age was 65 years (63% female). Baseline characteristics were comparable. Overall, 73% were treated with laminectomy and fusion. Follow-up was obtained in 84% of patients. Analysis at 6 months showed that patients with spinal expert review had a trend towards superior ODI outcome (23.7 point improvement with review vs. 18.1 point improvement without review; P = .06). In addition, there was a non-significant improvement in EQ-5D outcome at 6 months (0.258 improvement with review vs. 0.201 improvement without review; P = 0.11). ODI and EQ-5D outcomes for patients treated with decompression alone versus decompression and fusion were not different at 6 months. NASS patient satisfaction was graded as 1 (treatment met my expectations) in 75% of patients who had expert review as compared to 44% of cases when no panel review was used ( P = .08). CONCLUSION: Preliminary data from a randomized trial suggest that spinal expert review may generate improved patient reported outcomes and patient satisfaction for patients with lumbar degenerative spondylolisthesis. Further studies will be necessary to determine how the composition of spinal expert panels might influence these results.